(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
This study explores how green marketing influences the destination choice of shipping tourists, a segment where traveller’s increasingly seek sustainable experiences, but empirical evidence remains limited. This quantitative research employed a structured questionnaire and used R-based statistical techniques, including logistic regression, ROC analysis, and mediation analysis, on a sample of 325 shipping tourists to predict destination choice. The analysis confirmed excellent instrument reliability (alpha = 0.90) and found strong positive correlations between Green Marketing Awareness and Destination Choice (r=0.832); however, the logistic regression model found no statistically significant individual effects for the predictors, and the Causal Mediation Analysis failed to detect any significant direct or indirect effects. While the model showed fair overall discrimination (AUC = 0.7845) and an adequate fit (Hosmer-Lemeshow p > 0.05), its practical utility is severely limited by poor sensitivity (only 0.92% correctly classified true positives); therefore, future research must re-evaluate the binary measurement of Destination Choice and incorporate unobserved factors to enhance the predictive power of the model and generalizability of findings.